2021
DOI: 10.3390/insects12110996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resistance Development in Bemisia tabaci Genn. (Homoptera: Aleyrodidae) in Cotton against Different Insecticides

Abstract: Cotton is a major crop of Pakistan, and Bemisia tabaci (Homoptera: Aleyrodidae) is a major pest of cotton. Due to the unwise and indiscriminate use of insecticides, resistance develops more readily in the whitefly. The present study was conducted to evaluate the resistance development in the whitefly against the different insecticides that are still in use. For this purpose, the whitefly population was selected with five concentrations of each insecticide, for five generations. At G1, compared with the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The silverleaf whitefly B. tabaci is no exception, with median lethal concentrations of pymetrozine being increased approximately 11 times after 18 generations (Wang et al 2021). The recent results provided by Khalid et al (2021) are even more striking, as these authors reported a very high increase of the resistance level to buprofezin (127-fold) and imidacloprid (86-fold) after five generations only. A masterpiece case of rapid adaptation was conducted by Karasov et al (2010) in Drosophila demonstrating that organophosphate treatments quickly induced ace point mutations, resulting in multiple simple and complex resistant-ace alleles in the investigated fly subpopulations.…”
Section: Discussionmentioning
confidence: 94%
“…The silverleaf whitefly B. tabaci is no exception, with median lethal concentrations of pymetrozine being increased approximately 11 times after 18 generations (Wang et al 2021). The recent results provided by Khalid et al (2021) are even more striking, as these authors reported a very high increase of the resistance level to buprofezin (127-fold) and imidacloprid (86-fold) after five generations only. A masterpiece case of rapid adaptation was conducted by Karasov et al (2010) in Drosophila demonstrating that organophosphate treatments quickly induced ace point mutations, resulting in multiple simple and complex resistant-ace alleles in the investigated fly subpopulations.…”
Section: Discussionmentioning
confidence: 94%
“…The possible reasons in Pakistan scenarios, lack of speci ed resistance management schemes and injudicious use of insecticides are supposed to be the reasons in development of resistance in B. tabaci (Banerjee et al, 2014). The continuous relying on limited group of insecticides has lead and resulted in resistance development to B. tabaci (Khalid et al, 2021a).…”
Section: Resistance Monitoring Resultsmentioning
confidence: 99%
“…Judicious application of insecticides is essential (76), since a non-judicious and unnecessary use of pesticide has developed resistance in insect pests. Bemisia tabaci is the fifth most insecticide-resistant species in the world out of the top 12; therefore, the control of whitefly has become a global concern due to readily developing resistance against each new introduced insecticide (46). Indiscriminate use of insecticides against whitefly can only be stopped by the proper and timely pest scouting.…”
Section: Vector Management Through Insecticidesmentioning
confidence: 99%